Analisis Kepuasan Pengunjung Terhadap Kualitas Pelayanan Dengan Metode Customer Satisfaction Index (CSI) Dan Importance Performance Analysis (IPA): (Studi Kasus : Wisata Jatiwangi Park Dan Goa Djoyokusumo) - Anam, Khoirul; Wirawan, Novi Hendra; Kalista, Anggia; Anggraini, Susanti Dhini (Universitas PGRI Ronggolawe, 2022)
During the Covid-19 pandemic all countries in the world experienced difficulties, including Indonesia. A pandemic that hit the world has given a big change, especially tourism. Tuban Regency has many natural tourist attractions that present the charm of beauty. One of them is the tourist attraction Jatiwangi Park and Goa Djoyokusumo. In July 2021, the number of tourist visitors to Jatiwangi Park and Goa Djoyokusumo experienced a very drastic decline due to the PPKM for 3 months. To maximize income in the new normal era, it is necessary to carry out a human resource development program. One way is to know the satisfaction of visitors to the quality of service. Analysis that can be used to determine visitor satisfaction is the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). Based on the results of research that has been conducted on Jatiwangi Park and Goa Djoyokusumo tours, the conclusions obtained are as follows: a) Based on the results of the level of satisfaction and the level of importance of the Tangible, Reliability, Responsive, Assurance and Empathy dimensions, the interpretation of very satisfied ranges from 83.57% - 88.53% and the calculation of the Customer Satisfaction Index has an interpretation satisfaction level with an average of 86.90% showing very satisfied results. b) There are 2 attributes that need to improve the quality of service, namely opening and closing hours on time, there are adequate handwashing facilities and soap.